The diversity of non-volant small mammals in gragmented forest and oil palm plantation - Muhammad Hafizullah, Ikwan (Universiti Malaysia Sarawak (UNIMAS), 2015)
Cultivation of oil palm requires an enormous amount of forest to be logged and causes the disturbance in that habitat. It also causes the fragmentation of the forest. A diversity study of non-volant small mammals between fragmented forest and oil palm plantation was conducted in Saremas 2 Plantation in three sampling period: 12'" August until 21 a August 2014, 14th January until 21" January 2015 and 12'" April until 17th April 2015. The objective of this study was to determine the species diversity of non-volant small mammals in oil palm plantation and fragmented forest. Cage traps were used to catch the animals. 43 individuals from three families of Tupaiidae, Sciuridae and Muridae were caught. Eight species were captured in the forest while four species at the edge and seven species at the plantation. There is no significant difference in diversity of non-volant small mammals in fragmented forest and oil palm plantation.